Upaya Meningkatkan Motivasi Belajar Siswa Kelas IV Fase B Mengembangkan Kemampuan Diriku Secara Mandiri Melalui PBL Pada PAK di SDN 20 Tekudak Tahun Ajaran 2023 / 2024 - Restituta A.Wona (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research aims to describe the increase in student learning motivation. This research is a class action research carried out in two cycles. The subjects of this study were all grade IV students of SD Negeri 20 Tekudak, Kalis District, Kapuas Hulu Regency, West Kalimantan Province, totaling 14 students. The results of this study showed that, the number of learning motivation scores of first cycle students averaged 68.57%, and the average post-test score was 70.14. While in cycle 2, student learning motivation averaged 76.64% and post test scores 77.42. this shows that there is an increase, student learning motivation in each cycle after research is carried out through the problem Based Learning (PBL) model. Student learning motivation before participating in the learning process is still relatively low. Based on the results of the study, it can be concluded that the application of the Problem Based Learning model can increase student learning motivation.